Effect of Colostrum Education on the Intention of Third-Trimester Pregnant Women to Provide Colostrum: Pengaruh Edukasi tentang Kolostrum pada Ibu Hamil Trimester III terhadap Niat Ibu dalam Pemberian Kolostrum - Parahita, Anorraga; Pratamaningtyas, Susanti; Wijayanti, Lumastari Ajeng (JURNAL KEBIDANAN, 2024)
Introduction: Indonesia has the third-highest infant mortality rate in ASEAN. One of the causes is that infants are not given colostrum (containing antibodies), making them susceptible to infections such as pneumonia and diarrhea, which are the biggest contributors to mortality. Mothers who did not give colostrum often lacked sufficient information to influence their intention to give colostrum. This study aimed to determine the effect of education about colostrum in third-trimester pregnant women on mothers' intention to give colostrum. Method: The pre-experimental study used a one-group pre-posttest design with a sample size of 37 respondents. Data were collected using a questionnaire and analyzed by Mc. Nemar Test. Result: the results of respondents whose intention to give colostrum before education was 48.6% and after education was 97.3%. Statistical tests showed ρ value = 0.000 < α = 0.05, so there was a significant difference between the intention to give colostrum before and after the intervention. Discussion: This shows that there is an effect of education about colostrum in third-trimester pregnant women on the mother's intention to give colostrum.